Sistem Informasi Pemesanan Pecel Sayur Berbasis Website - Anggun Mustika Sari; Muhamad Bahrul Ulum (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
The importance of information technology for customers cannot be overstated. It plays a crucial role in helping individuals streamline their work processes and access the necessary information. Hence, this study has developed a website-based ordering system for vegetable